2002
DOI: 10.1001/archinte.162.10.1117
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-Triggered vs Fixed-Schedule Doses of Benzodiazepine for Alcohol Withdrawal

Abstract: Symptom-triggered benzodiazepine treatment for alcohol withdrawal is safe, comfortable, and associated with a decrease in the quantity of medication and duration of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
148
3
6

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(163 citation statements)
references
References 15 publications
6
148
3
6
Order By: Relevance
“…Subsequent to that report, numerous studies have investigated route, dose, and method of administration. Specifically, administration of benzodiazepines in a symptom-triggered fashion results in less benzodiazepine utilization and shorter duration of therapy (4,5). However, these trials focused on subjects with relatively mild to moderate withdrawal who were stable enough to be treated in detoxification facilities or on the general medical ward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent to that report, numerous studies have investigated route, dose, and method of administration. Specifically, administration of benzodiazepines in a symptom-triggered fashion results in less benzodiazepine utilization and shorter duration of therapy (4,5). However, these trials focused on subjects with relatively mild to moderate withdrawal who were stable enough to be treated in detoxification facilities or on the general medical ward.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies suggest that administration of benzodiazepines in a symptom-triggered fashion both reduces the total amount of benzodiazepine administered and shortens the duration of therapy (4,5). In these studies, benzodiazepines are administered in repeated boluses (both intravenous and oral) of 10-20 mg of diazepam (or benzodiazepine equivalent) with current recommendations suggesting a maximal individual bolus of 20-30 mg of diazepam or benzodiazepine equivalent to be given until adequate sedation is achieved (4,6,7). Although widely accepted, these studies focus primarily on patients admitted to detoxification centers or the general hospital wards and exclude subjects admitted to the intensive care unit (ICU) (4,5).…”
mentioning
confidence: 99%
“…Such symptom-triggered treatment is generally preferred over fixed-dose regimens, 15 in part because when using this method, many cases of AWS can be managed with less medication. Benzodiazepine regimens using high doses have been found to be associated with substantial morbidity and prolonged hospitalizations.…”
mentioning
confidence: 99%
“…These include the ability to individualise treatment, reduction in treatment duration and reduced occurrence of delirium tremens [1,4]. Previous studies have shown equally efficacious results with a symptom triggered approach [5]. There is, however, a requirement of suitably trained staff [1].…”
Section: Introductionmentioning
confidence: 99%